The Extraction of Curcuminoids From Ethanol Extract of Yellow Turmeric (Curcuma longa L) and Activity Test on P-388 Murine Leukemia Cells - Ida Wati; Vibianti Dwi Partiwi; Maya Ramdianti Musadi (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
Abstract: Research on the Extraction of Curcuminoids from Ethanol Extract of Yellow Turmeric (Curcuma longa L) and its Activity Test on P-388 Murine Leukemia Cells has been carried out. This study aims to determine the per cent yield, solvent concentration, activity of P-388 murine leukemia cells and pH of the number of curcuminoids produced in ethanol extract. The curcuminoids were obtained by the extraction process through the soxhlet method using 70 and 96% ethanol solvent with a ratio of sample to solvent of 1:8 with variations in operating time for 3, 6, 9 and 12 hours. The absorbance of curcuminoid extract was measured to determine the concentration of curcumin. The cytotoxic test on murine leukemia P-388 cells used the Microculture Tetrazolium Technique (MTT) method. The results obtained were yellow turmeric curcuminoid compounds using 96% ethanol solvent at an extraction operating time of 9 hours. The largest extract yield was 21.15% with a concentration of 1121.10 ppm, which has activity against murine leukemia P-388 cells with an IC50 of 6.15 g/mL have the potential as anticancer leukemia, and dye analysis at acidic pH (2,4,6) is yellow, while alkaline pH (9,12) is brownish red as a natural food coloring.Abstrak: Penelitian ekstraksi kurkuminoid dari ekstrak etanol kunyit kuning (Curcuma longa L) dan uji aktivitasnya terhadap sel murine leukimia P-388 telah dilakukan. Penelitian ini bertujuan untuk mengetahui rendemen, konsentrasi pelarut, aktivitas sel murine leukemia P-388 dan pH terhadap jumlah kurkuminoid yang dihasilkan pada ekstrak etanol. Kurkuminoid diperoleh dengan proses ekstraksi dengan metode sokletasi menggunakan pelarut etanol 70 dan 96% dengan perbandingan sampel dan pelarut 1:8 variasi waktu operasi selama 3, 6, 9 dan 12 jam. Ekstrak kurkuminoid diukur absorbansi untuk mengetahui konsentrasi kurkumin. Pengujian sitotoksik terhadap sel murine leukimia P-388 dengan metode Microculture Tetrazolium Technique (MTT). Hasil yang diperoleh senyawa kurkuminoid kunyit kuning menggunakan pelarut etanol 96% pada waktu operasi ekstraksi 9 jam rendemen ekstrak terbesar 21,15% dengan konsentrasi 1121,10 ppm, memiliki aktivitas terhadap sel murine leukimia P-388 dengan IC50 sebesar 6,15 μg/mL berpotensi sebagai antikanker leukemia, dan analisis zat warna pada pH asam (2,4,6) berwarna kuning, pada pH basa (9,12 ) berwarna merah kecoklatan sebagai pewarna alami makananan.